Design of a Solar Cell Power Generation System for Utilizing Fuel on Ships - Agus Priyanto; Diah Zakiah; Damoyanto Purba; Retno Sawitri Wulandari (Dinasti International Journal of Education Management And Social Science, 2024)
The aim of this research is to determine the design of a solar cell power generation system for utilizing fuel on ships at PT. Universal Manunggal Chakra. In this research, the type of research used is Research and Development. Seeing these things, researchers are interested in developing a solar cell power generation system to supply electricity on ships and applying a solar cell power generation system to supply electricity on ships. The results of the research state that the results of the manufacture and development of a prototype solar cell power generator can be concluded that the product is suitable, so it can be applied on ships. This can be proven from the test results by having a percentage of 96.25% in the appropriate category, so that the power generator prototype can supply electricity to the diesel generator on the MT.Hendropriyono III ship.